Pelatihan Pembuatan Modul Ajar sebagai Upaya Implementasi Kurikulum Merdeka pada Guru SDN Jatirejo Kabupaten Kediri - Wenda, Dhian Dwi Nur; Permana, Erwin Putera; Damariswara, Rian; Imron, Ilmawati Fahmi; Putri, Kharisma Eka; Sahari, Sutrisno; Kurnia, Ita; Handayani, Rizky; Wiganata, Siken Agil (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Most of the elementary school teachers in the Kediri District, Mostly, have not been able to compile teaching modules for the independent curriculum. It is necessary to provide training in the preparation of teaching modules. The method used there are three stages, namely planning, implementation, and evaluation. The training went smoothly and well. The material provided was easily understood by 68.2% of the participants. As many as 45.5% of participants stated that the speaker was very clear. As many as 79.5% of participants required further training. In addition to containing percentages, the participants wanted a longer training time, added facilitators or companions for the training participants, and simplified the training material.